Exploring the Genetic Landscape of Mycobacterium tuberculosis: Unlocking the Differences in Between Latent and Active Tuberculosis - Ali Akbar Velayati; Satoshi Mitaria; Parissa Farnia; Poopak Farnia; Jaladein Ghanavi; Mohsan Maleknia; Yoshiro Murase; Sven Hoffner (International Journal of Mycobacteriology)
Background: Tuberculosis (TB), caused by Mycobacterium tuberculosis (MTB), can enter a dormant phase within host tissues, complicating treatment and highlighting the need to investigate the genetic changes associated with dormancy. Methods: This study examined clinical isolates of MTB, representing a range of susceptibility profiles and standard reference laboratory strains, i.e., H37Rv and Mycobacterium bovis bacillus Calmette–Guérin. Each strain was subcultured in a controlled laboratory environment to analyze two distinct phases: one maintained in vitro under a double-stress dormancy model using the Wayne model (characterized by the absence of oxygen and nutrients) for 12 months, and the other examined during its exponential growth phase. Whole-genome sequencing and protein structure analysis using bioinformatics tools were performed to characterize and compare mutations in isolates at each phase. Results: Three distinct frameshift mutations were identified in the fbiC, PPE35, and ald genes, and one upstream mutation in whiB6 genes in all studied isolates under dormancy, irrespective of their susceptibility patterns (P < 0.01). Among drug-resistant strains, at the exponential phase isolated from patients with prolonged treatment, 5%–7% had PPE35, ald mutations, whereas 95% had the whiB6 mutation, suggesting that adaptive stress responses may be triggered under in vivo conditions. Conclusions: The newly identified frameshift mutations (fbiC, PPE35, and ald genes), consistently found in both laboratory and clinical isolates, seem to play a critical role in the survival of MTB during dormancy. Based on these findings, designing a molecular test to differentiate between active and latent TB possibly enables timely prophylactic interventions.